Diccionario del universo vocabulario de los niños y niñas achuar para profesores y estudiantes de la educación general básica. - Jeencham Rumpik, Titia Benjamín (2018)
This research has been done by consulting different bibliographical sources and making observation of the field, with the sole purpose of elaborating a dictionary of the vocabulary universe of the children-achuar teachers and students of basic general education, so that they serve as a source of the consult your concerns in different levels and subjects related to language. This product was developed according to the needs of students of basic general education of bilingual schools, the books that are produced from "outside" comes decontextualized from the social context and the mother tongue, because they have little application in schools, but This material will serve as a great support for teaching and learning.